Pengaruh Strategi Pembelajaran Inkuiri Terhadap Minat Belajar Siswa Pada Mata Pelajaran Pendidikan Agama Kristen dan Budi Pekerti Kelas IX SMP N 2 Tarutung Tahun Pembelajaran 2022/2023 - Comen Manurung (Jurnal Sadewa : Publikasi Ilmu Pendidikan, Pembelajaran dan Ilmu Sosial, 2023)
The purpose of this study is to determine the Effect of Inquiry Learning Strategies on the Learning Interests of PAK Students and Class IX Ethics of SMP N 2 Tarutung Learning Year 2022/2023. The research method used is quantitative method. The population is all grade IX students of SMP Negeri 2 Tarutung totaling 179 people and a sample of 32 people was determined using the Purposive Sample technique. Data was collected using a positive closed questionnaire of 48 items, namely 20 items for variable X and 28 items for variable Y. The results of data analysis showed that there was a positive and significant influence of inquiry learning strategies on learning interest in the subjects of Christian Religious Education and Ethics grade IX SMP N 2 Tarutung Learning Year 2022/2023: 1) Test analysis requirements: a) positive relationship test obtained rxy value = 0.609 > rtable(=0.05,n=32) = 0.349. b) Significant relationship test obtained tcount value = 4.211 > ttable(=0.05,dk=n-2=30)= 2.042. 2) Influence test: a) Regression equation test, obtained regression equation Y ̂="20.49"+1.11X. b) Regression coefficient of determination test (r2) = 37.1%. 3) Test the hypothesis using the F test obtained Fcalculate > Ftable=(=0.05,dk numerator k=14,dk denominator=n-2=32-2=30) which is 17.69 > 2.01. Thus Ha is accepted and H0 is rejected.